Template-based Treemaps to preserve spatial constraints - Natallia Kokash; Bernard de Bono; Joost Kok (IVAPP'14: Proceedings of the International Conference on Information Visualization Theory and Applications, 2014)
Treemapping is a method for displaying hierarchical data using nested rectangles. Each branch of the tree is given its rectangle, which then is tiled with smaller rectangles representing sub-branches. A node's shape has an area proportional to a specified dimension of the data. To create a treemap, one must define a tiling algorithm, i.e., a way to divide a rectangle into sub-rectangles of specified areas. There are several problems with existing tiling algorithms: (i) they allow tiles to shift when the main window or some of the tiles are resized affecting the user perception of the information; (ii) they do not allow users to place selected elements into desired positions w.r.t. each other. In this paper, we present a method for creating treemaps with customized layouts. The method is based on reusable templates and supports zooming into specific areas of the treemap without affecting its initial layout. We illustrate the use of template-based treemaps to the visualization of biome dical data. Furthermore, we present an algorithm for automated generation of layouts satisfying positional constraints for a particular class of constraints.